2002
DOI: 10.1177/002215540205000202
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and Androgenic Regulation of the Immunocytochemical Distribution of mK1, a True Tissue Kallikrein, in the Granular Convoluted Tubule of the Mouse Submandibular Gland

Abstract: S U M M A R YThe action of androgens on the immunocytochemical distribution of mK1, a true tissue kallikrein, was examined in the submandibular gland (SMG) of developing and adult mice by indirect enzyme-labeled and immunogold-labeled antibody methods for light and electron microscopy, respectively. In both sexes at 3 weeks of age, essentially all of the immature granular convoluted tubule (GCT) cells were uniformly immunostained. At 4 weeks of age (the onset of puberty), morphological differences between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 27 publications
3
34
0
Order By: Relevance
“…Very small secretory granules were usually mixed among large secretory granules in the above-described GCT cells that were increased in size by the hormone injections (Fig. 4a-c), as well as in the GCT cells of normal mice of both sexes (see our previous articles 8,9,11,12 ). However, small secretory granules were less abundant in the cells containing a few huge secretory granules in the group injected with all three hormones (Fig.…”
Section: Hormonal Replacementmentioning
confidence: 58%
See 1 more Smart Citation
“…Very small secretory granules were usually mixed among large secretory granules in the above-described GCT cells that were increased in size by the hormone injections (Fig. 4a-c), as well as in the GCT cells of normal mice of both sexes (see our previous articles 8,9,11,12 ). However, small secretory granules were less abundant in the cells containing a few huge secretory granules in the group injected with all three hormones (Fig.…”
Section: Hormonal Replacementmentioning
confidence: 58%
“…These morphological characteristics are almost the same as those of the developing GCT cells of perinatal (lactational) mice. [7][8][9]11,12 Our previous immunocytochemical studies suggested that all GCT cells of hypophysectomized mice and of perinatal mice are mK1-immunoreactive, whereas most of the GCT cells in mature male SMGs, and approximately one-third of GCT cells in mature female SMGs do not synthesize mK1. 9,11,12 mK1 is a member of the kallikrein gene family and has been identified as a true tissue kallikrein.…”
Section: Discussionmentioning
confidence: 99%
“…Cells expressing EGF is less abundant in the GCTs of adult female SMGs (van Noorden et al, 1977;. GCT cells expressing a true tissue kallikrein, mK1, are less abundant in the SMGs of male than female mice (Kurabuchi et al, 1999(Kurabuchi et al, , 2002, and cellular mosaic expression of mK1 is also observed in the SLG of adult male mice (Kurabuchi et al, 2000). These findings suggest that GCT cells, all of which possess the same ultrastructural appearance, are not uniform in terms of producing the same secretory products.…”
Section: Discussionmentioning
confidence: 99%
“…All immature GCT cells expressed mK1, but the inhibition of mK1 was observed at 4 weeks of age, corresponding to the onset of puberty. Nearly all the SMG GCT cells in adult male mice expressed EGF, NGF and renin, while less than 1% of the population of GCT cells expressed mK1 (13). Therefore, mK1 appears to be a neonatal type of secretory product that is down-regulated by pituitary-dependent hormones ; this unusual characteristic differs from that of other GCT-specific secretory products.…”
Section: Characterization Of Hormone-in-duced Gct-like Cellsmentioning
confidence: 92%